Analysis of the Impact of Smartphone on Cognitive-Domain Mathematics Learning Outcomes in Grade VI Elementary School - Suryaningsih, Intan; Khamdun, Khamdun; Riswari, Lovika Ardana (Jurnal Pendidikan Matematika Universitas Lampung, 2026)
Smartphone use among elementary school students is increasingly widespread, but is often misused for entertainment rather than learning. This is feared to affect learning outcomes, especially in mathematics. This study aims to analyze the impact of smartphone use on the cognitive domain of sixth-grade students' mathematics learning outcomes. This study uses a qualitative approach with a case study type. The research subjects consisted of five sixth-grade students with high, medium, and low learning outcomes categories, as well as sixth-grade teachers. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out through data collection, data reduction, data presentation, and conclusions. The results of this study indicate that students with high learning outcomes use smartphones as a learning support tool so that it does not interfere with conceptual understanding. For students with medium learning outcomes, smartphones have a dual impact, namely helping in searching for information but also reducing learning focus. Meanwhile, for students with low learning outcomes, the dominant use of smartphones for entertainment has a negative impact on concentration, conceptual understanding, and independence in solving math problems. The conclusion of this study is that smartphones have a significant impact on students' mathematics learning outcomes, especially in the cognitive domain for students with high, medium, and low learning outcomes. The impact is dual in nature, namely it can be a supporter or an obstacle to learning, depending on the intensity, goals and how students utilize it.